Decision regret after radical prostatectomy does not depend on surgical approach: 6-year followup of a large German cohort undergoing routine care - Baunacke, Martin; Schmidt, Maria-Luisa; Groeben, Christer; Borkowetz, Angelika; Thomas, Christian; Koch, Rainer; Chun, Felix K. H.; Ihrig, Andreas; Weißbach, Lothar; Huber, Johannes (The journal of urology, 2020)
Purpose: Numerous studies have compared the outcomes of open and robot-assisted radical prostatectomy but to our knowledge only 1 study has focused on patient satisfaction and regret. We evaluated intermediate term decision regret after open and robot-assisted radical - prostatectomy. Materials and Methods: The HAROW (Hormonal Therapy, Active Surveillance, Radiation, Operation, Watchful Waiting) study analyzed localized prostate cancer treatments (T2c N0 M0 or less) in Germany from 2008 to 2013. We collected intermediate term followup data on 1,260 patients after retropubic open or robot-assisted radical prostatectomy. Results: The response rate was 76.8% (936 of 1,218 cases). A total of 404 patients underwent robot-assisted radical prostatectomy and 532 underwent open radical prostatectomy. - Patients treated with the robot-assisted procedure showed more self-determined behavior. They reported an active role in surgical decision making and the surgical approach (robot-assisted radical vs open prostatectomy 39% vs 24% and 52% vs 18%, respectively, each p <0.001). Patients treated with the robot-assisted procedure more often participated actively in selecting the treating hospital (25% vs 11%), used the Internet often (87% vs 72%) and traveled an increased distance (63 vs 42 km, all p <0.001). Overall decision regret was low with a mean ± SD score of 14 ± 19 on a scale of 0—no regret to 100—high regret. Multivariate analysis showed that erectile function (OR 3.2), - urinary continence (OR 1.8), freedom from recurrence (OR 1.6), an active decision making role (OR 2.2) and shorter followup (OR 0.9 per year) predicted low decision regret (score less than 15). Conclusions: Intermediate term functional and oncologic outcomes as well as autonomous decision making and followup time influenced decision regret after radical prostatectomy. The surgical approach was not associated with intermediate term decision regret.
Gesehen am 14.04.2020